Antibiotic Susceptibility in Biofilms of Mycobacterium smegmatis - Sachan, Tarun Kumar; Kumar, Virendra (International Journal of Applied Sciences and Biotechnology, 2015)
In the present article we observed the quantification and morphological, ultrastructural features of biofilms of fast growing clinical isolates M. smegmatis in presence of first line antibacterial drug streptomycin, isoniazid rifampicin, ethambutol and pyrazinamide. Biofilm of M. smegmatis was found to be unaffected at concentration of drugs that inhibited growth of planktonic bacilli .Thus, the biofilm growth modus appears to be a strategy for replicating bacilli to evade the trap of antibacterials. Planktonic and biofilm cells had similar intrinsic antibiotic susceptibility. Electron microscopy revealed that control (no drug) biofilms consisted primarily of bacterial clusters and fibrillar elements. The extracellular polymeric substance (EPS) material was less abundant in antibiotic-treated than in control biofilms beacause in the presence of high antibiotic concentrations at MIC level. The study is explored that the effect of drug on biofilm is time dependent means if the drugs were added at initial phase of biofilm, significant inhibitory effect were observed. Int J Appl Sci Biotechnol, Vol 3(4): 635-641